Mapping the OA Diamond landscape worldwide. What do we know so far? - Proudman, Vanessa (Septentrio Conference Series, 2020)
See RECORDING. The open access publishing offering has grown significantly over the last two decades with DOAJ alone currently indexing over 15,000 open access journals. Apart from APC-based OA, a fertile and diverse landscape of open access journals and platforms exists in the form of Diamond OA. Diamond OA is the publishing model where research is both free for authors to publish and free for readers to access. This presentation will describe the results of an ongoing research study: The Diamond Open Access Study commissioned by cOAlition S. This research study aims to acquire a deeper understanding of the landscape of OA Diamond journals and platforms. Its goal is also to gain insights that will help cOAlition S and other stakeholders develop effective policies and funding mechanisms that more strategically support Diamond Open Access. For the Munin Conference, we aim to present the preliminary results of the survey part of the study. As at end August, more than 1,700 Diamond OA journals have responded to the survey which was launched in early July 2020. The survey focuses on journals in DOAJ and on those not yet included. The session will address the following: What are the motivations for OA Diamond? How mature are OA Diamond journals, where are they based, what languages and what disciplines do they serve? What journal services are provided? How do journals manage copyright and licensing? What editorial quality assurance practices exist? And how do these characteristics differ between journals from different regions, languages and disciplines? Who owns them? How are they funded, by whom and using which type of mechanism? What revenue streams exist? How might funders support the financial sustainability of the journal or platform?